2019
DOI: 10.1016/j.pediatrneurol.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous Sclerosis Complex Genotypes and Developmental Phenotype

Abstract: Background: Children with tuberous sclerosis complex (TSC), caused by pathogenic variants in TSC1/TSC2, are at risk for intellectual disability. TSC2 pathogenic variants appear to increase the risk, compared with TSC1. However, the effect of TSC2 pathogenic variants on early and specific domains of development hasn’t been studied. Using an extensively phenotyped group, we aimed to characterize differences in early intellectual development between genotypes. Methods: The study group (n = 92) included particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
1
17
1
3
Order By: Relevance
“…It was first found that the TSC1/TSC2 group reported significantly worse QOL. Similar to previous studies, TSC1/TSC2 pathogenic variants could generally cause a more severe clinical phenotype 4,24‐28 …”
Section: Discussionsupporting
confidence: 88%
“…It was first found that the TSC1/TSC2 group reported significantly worse QOL. Similar to previous studies, TSC1/TSC2 pathogenic variants could generally cause a more severe clinical phenotype 4,24‐28 …”
Section: Discussionsupporting
confidence: 88%
“…5,10,28 In a recent prospective study, Farach et al observed that infants with a TSC2 pathogenic variant had significantly lower developmental scores at age 24 months, independent of seizures. 29 In this study, early Vigabatrin treatment initiated before seizure onset did not significantly decrease the risk of ASD at 24 months, when compared to conventional treatment.…”
Section: Discussionmentioning
confidence: 53%
“…We are aware of only one other recent report of genetic analysis in a cohort of TSC infants. 24 There were several important observations in the present genetic analysis of the EPISTOP cohort.…”
Section: Discussionmentioning
confidence: 86%